Magnetic-field-tuned charge density wave in SmNiC2 and NdNiC2. (29th December 2016) - Lei, Hechang; Wang, Kefeng; Petrovic, C
Abstract: We report magnetic field tuned competition between magnetic order and charge density wave (CDW) states in SmNiC2 and NdNiC2 polycrystals. The destruction of CDW can be observed not only in SmNiC2 below ferromagnetic (FM) but also in NdNiC2 below antiferromagnetic (AFM) transition temperature. Moreover, the CDW states near magnetic transition temperatures can be tuned by the magnetic field for both compounds. Magnetic-field induced FM state in NdNiC2 is more effective in weakening the CDW than the AFM state at temperatures near Neel temperature T N but both ordering states have the same effect on CDW below T N . The interplay between magnetic and CDW states in SmNiC2 and NdNiC2 may be different, suggesting that these materials are good models to study correlations between magnetic and CDW wave order.